Aggressive behaviour and physiological responses to pheromones are strongly impaired in mice deficient for the olfactory G‐protein γ‐subunit Gγ8. (25th July 2013) - Montani, Giorgia; Tonelli, Simone; Sanghez, Valentina; Ferrari, Pier Francesco; Palanza, Paola; Zimmer, Andreas; Tirindelli, Roberto
Key points: Pheromones are intraspecies chemical signals that take part in the sexual recognition and choice of appropriate mating partners. In the vomeronasal organ (VNO), pheromone responses are probably triggered by two distinct neuronal populations, respectively expressing the heterotrimeric G‐proteins Gαi2β2γ2 and Gαoβ2γ8 that, in turn, coexpress with two pheromone receptor families, V1R and V2R. We demonstrate that the olfactory‐specific G‐protein γ8 subunit (Gγ8) plays an important role in pheromone‐dependent socio‐sexual recognition. Deficient mice for Gγ8 show a marked reduction in the pheromone‐mediated aggressive behaviour in both females and males that corresponds with a failure to activate V2R targets in the brain. These effects occur in combination with a consistent loss of vomeronasal neurons. Thus, Gγ8 is essential for maintenance of the neuronal population of the VNO and for correct transduction of the pheromonal signal. Abstract Heterotrimeric G‐proteins are critical players in the transduction mechanisms underlying odorant and pheromonal signalling. In the vomeronasal organ (VNO) of the adult mouse, two different G‐protein complexes have been identified. Gαoβ2γ8 is preferentially expressed in the basal neurons and coexpresses with type‐2 vomeronasal pheromone receptors (V2Rs) whereas Gαi2β2γ2 is found in the apical neurons and coexpresses with type‐1 vomeronasal pheromone receptors (V1Rs). V2R‐expressing neurons project to the posterior accessory olfactory bulb (AOB) whereas neurons expressing V1Rs send their axon to the anterior AOB. Gγ8 is also expressed in developing olfactory neurons where this protein is probably associated with Go. Here, we generated mice with a targeted deletion of the Gγ8 gene and investigated the behavioural effects and the physiological consequences of this mutation. Gγ8 −/− mice show a normal development of the main olfactory epithelium; moreover, they do not display major deficits in odour perception. In contrast, the VNO undergoes a slow but remarkable loss of basal neurons starting from the fourth postnatal week, with a 40% reduction of cells at 2 months and 70% at 1 year. This loss is associated with a reduced early‐gene expression in the posterior AOB of mice stimulated with pheromones. More interestingly, the Gγ8 deletion specifically leads to a reduced pheromone‐mediated aggressiveness in both males and females, all other socio‐sexual behaviours remaining unaltered. This study defines a specific role for Gγ8 in maintenance of the neuronal population of the VNO and in the mechanisms of pheromonal signalling that involve the aggressive behaviour towards conspecifics.